Sustainable Development from Within: Empowering Communities through Financial Empowerment and SME Support - Noch, Muhammad Yamin; Rumasukun, Mohammad Ridwan (Manunggal Halim Jaya, 2023)
This study explores the intersection of SME development, community empowerment, and financial support mechanisms, aiming to uncover insights for fostering inclusive economic growth and resilience within grassroots communities. Employing a qualitative research approach, the study conducts a systematic literature review to analyze scholarly works, theoretical perspectives, and empirical studies related to the topic. The literature selection process involves searching academic databases and employing snowball sampling techniques to ensure comprehensive coverage. Data collection entails critical reading, note-taking, and coding of textual data, with NVivo software used for data organization. Thematic analysis is employed to identify recurring themes and theoretical frameworks across the literature, shedding light on the transformative potential of financial support programs for SMEs. The study highlights the pivotal role of microfinance, venture capital, and government subsidies in addressing funding constraints faced by SMEs, while also recognizing challenges such as high-interest rates and bureaucratic inefficiencies. Moreover, it underscores the importance of community empowerment in shaping the enabling environment for entrepreneurship and economic growth. Empowered communities are better positioned to leverage external resources and initiatives for collective benefit, thereby enhancing resilience and well-being. The findings emphasize the need for targeted interventions, institutional reforms, and partnerships to promote SME development and community empowerment effectively.